ANALISIS NILAI MORAL DALAM NOVEL SELAMAT TINGGAL KARYA TERE LIYE - Rizky Nathasya Putri; Sumiharti Sumiharti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the moral value of positive thinking aspects in the novel Selamat Tinggal by Tere Liye, aspects of helping others, aspects of true love, aspects of helping the weak selflessly, aspects of mutual respect and aspects of knowing each other in the novel. The type of research used by the author in this study is descriptive research, the problem formulated must be feasible to raise, contain scientific value, and not be too broad, qualitative research is a result of analytical procedures. Using descriptive qualitative research, the author can describe and describe the moral values in the novel Selamat Tinggal by Tere Liye. The source of research data is where the data is found, the data source of this research is sourced from a novel entitled Selamat Tinggal by Tere Liye published in 2021 in its seventh printing, totaling 360 pages. This novel has a pictorial blue cover, published by Gramedia Pustaka Utama Publisher. The author bought this novel at the Gramedia bookstore in Jambi city. Data collection techniques by reading source books related to literary theory, as well as source books related to moral values, the author looks for the novel Selamat Tinggal by Tere Liye, the author reads carefully the novel, and the author marks the findings in the form of quotes related to the moral values contained in the novel. In this study, the author can conclude that the novel Selamat Tinggal by Tere Liye consists of 32 values in which there are moral values using Wicaksono's theory.